2003
DOI: 10.1007/s00228-003-0683-2
|View full text |Cite
|
Sign up to set email alerts
|

Error reduction: academic detailing as a method to reduce incorrect prescriptions

Abstract: Academic detailing appears to be a useful method of reducing erroneous hospital prescriptions; and, to our knowledge, this is a novel finding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 6 publications
0
32
0
1
Order By: Relevance
“…Ten educational interventions were targeted at general practitioners (GPs),25 29 30 32–34 40 44 46 63 10 were conducted in hospitals,41 45 52 59 61 62 65–67 69 six were implemented at primary healthcare clinics/facilities,36–38 43 60 70 20 interventions were incorporated within the curriculum at universities18 26–28 31 39 42 47–51 53–58 64 68 and one intervention was carried out in pharmacies 35. These studies were conducted in numerous countries around the world (table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ten educational interventions were targeted at general practitioners (GPs),25 29 30 32–34 40 44 46 63 10 were conducted in hospitals,41 45 52 59 61 62 65–67 69 six were implemented at primary healthcare clinics/facilities,36–38 43 60 70 20 interventions were incorporated within the curriculum at universities18 26–28 31 39 42 47–51 53–58 64 68 and one intervention was carried out in pharmacies 35. These studies were conducted in numerous countries around the world (table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies evaluated the impact of educational interventions on the rate of prescribing errors using an audit of medication charts before and after the intervention 41 45 52 61 65–67. Multidisciplinary interventions using interrelated educational and behavioural modification strategies significantly reduced prescribing errors 65 66.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Academic detailing has been shown to reduce hospital prescribing errors. 17 However, a recent review concluded that published evidence regarding the impact of educational strategies on improving prescribing errors is limited. Published studies, in general, were of brief interventions with short follow-up periods and lacked testing in 'real-life' situations.…”
Section: Intervention Designmentioning
confidence: 99%
“…1 However, little has been published on the effectiveness of providing education and feedback to institutional clinicians to reduce prescribingrelated errors. [6][7][8] Providers often are already aware of ''classic'' medication order errors, but at most institutions, specific examples of prescribing errors are not regularly communicated from the pharmacy dispensary to prescribers. One exception occurs when a dispensary pharmacist contacts a prescriber to clarify an order.…”
mentioning
confidence: 99%